Assessing the core competencies of professional librarians working in public libraries of Punjab, Pakistan. - Abida Raza, Manzoor Raza (IJoLIS, 2025)
Purpose: This study “Assessing the ALA core competencies of professional librarians working in public libraries of central Punjab” was conducted to examine the library professionals’ competencies. The main objective of the study was to find out the gap in the competencies of professional librarians in the light of ALA core competencies standards. The first four competencies of ALA were disused in this study. Design/methodology/approach: The research was conducted by adopting quantitative research method. The population of this study was professional librarians working in public libraries of central Punjab. There are 53 library professional working in public libraries of central Punjab. The questionnaire was sent to 53 library professionals. Among them 45 library professionals returned the questionnaire correctly, with a response rate of 84.9%. Delimitation: only public libraries in central Punjab were the population of the study. Key finding(s): Data collected through questionnaire was arranged and entered for analysis and SPSS was used to analyze the data. Descriptive statistics were applied to calculate the mean, percentage and frequencies. The findings reveal that the participants’ perceived competencies were at intermediate level. The major problem of public libraries was the lack of professional staff. Practical implication (s): The findings of the study indicate that there is a need to revise the LIS curriculum under the light of ALA core competencies standards. It is recommended that there should be proper recruitment policies for the selection of public libraries’ staff. Paper type: Research